Pengaruh Kualitas Layanan Delivery Order Dan Cita Rasa Kopi Terhadap Repeat Order Di Tomoro Coffee Cabang Pamulang - Selvi Herliyani; Ria Aulia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of delivery order service quality and coffee taste on repeat orders at Tomoro Coffee Pamulang Branch. The research employed a quantitative approach using a survey method. Data were collected through online questionnaires distributed to 42 respondents who had previously used Tomoro Coffee's delivery order service. The data were analyzed using descriptive statistics, multiple linear regression, Pearson correlation, and hypothesis testing. The results indicate that delivery order service quality has a positive and significant effect on repeat orders, with a Pearson correlation coefficient of 0.708 and a significance value of 0.000. Coffee taste also has a positive and significant effect on repeat orders, with a Pearson correlation coefficient of 0.840 and a significance value of 0.000. Furthermore, coffee taste demonstrates a stronger influence on repeat orders compared to delivery order service quality. These findings suggest that maintaining consistent coffee taste and improving service quality are essential strategies for increasing customer repeat orders. Therefore, Tomoro Coffee should continuously enhance delivery service performance and product quality to strengthen customer loyalty and encourage sustainable repeat purchasing behavior.